Analysis of accuracy of the beginning of hijriah months reckoning of ad-Dur al-Aniq book in 20 years - Muchamad Choirun Nizar; Bashori Alwi (Sultang Agung Islamic University, 2020)
In the treasures of the development of astronomy and the method of reckoning in Indonesia, there are several classical Islamic astronomy (falak) books with various methods such as the book Sulam an-Nayyirain, Syamsul Hilal, Durus al-Falakiyyah, Nurul Anwar, and so on. One of the interesting things to study is the book Ad-Dur al-Aniq by KH. Ahmad Ghozali Muhammad Fathullah, an expert in astronomy who came from Madura, the book which is declared as a modern Islamic astronomy book with the method of reckoning tahqiq bi at-tadqiq. This method of reckoning tahqiq bi at-tadqiq is the most accurate because it has a long process and there are many interpolations. The calculation of reckoning for the beginning of the Hijri month in this book goes through 4 main stages, namely the calculation of ijtima, the time of sunset, the position of the sun, and the moon at sunset, and the conclusion of the reckoning. At each stage, it also consists of several counting processes and ta’dil. Through the calculation process, it can be proven that the calculation method in the book ad-Dur al-Aniq is included in the category of the tahqiqi bi at-tadqiq method with a very long algorithm and several corrections so that it gets very accurate results. The theory and calculation system are based on modern astronomical formulas (spherical trigonometric theory) and use a scientific calculator or computer as a calculation tool. After comparing the calculation results using the Jean Meeus algorithm and NASA SKYCAL, the result is that the average difference between the three calculations is no more than 2 minutes.